2017
DOI: 10.3832/ifor2181-010
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting multi-taxa diversity patterns between abandoned and non-intensively managed forests in the southern Dolomites

Abstract: The abandonment of silvicultural activities can lead to changes in species richness and composition of biological communities, when compared to those found in managed forests. The aim of this study was to compare the multi-taxonomical diversity of two mature silver fir-beech-spruce forests in the southern Dolomites (Italy), corresponding to the European Union habitat type 9130. The two sites share similar ecological and structural characteristics, but differ in their recent management histories. In the last 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
(48 reference statements)
4
7
0
Order By: Relevance
“…This is congruent with the low functional diversity in control plots (i.e., closed forests), suggesting that the available functional space, in terms of the ecological niche concept, are already held mainly by carnivorous forest specialist carabids with low dispersal capacity (Nolte et al 2017). The relatively homogeneous forest stand with closed canopy can prevent the establishment of more opportunistic carabids and ensure the persistence of forest specialists, which provides the functional stability of forest ecosystems (Sitzia et al 2017).…”
Section: Taxonomical Measures Reflect Between-year Differences and Variation In Assemblage Compositionsupporting
confidence: 52%
“…This is congruent with the low functional diversity in control plots (i.e., closed forests), suggesting that the available functional space, in terms of the ecological niche concept, are already held mainly by carnivorous forest specialist carabids with low dispersal capacity (Nolte et al 2017). The relatively homogeneous forest stand with closed canopy can prevent the establishment of more opportunistic carabids and ensure the persistence of forest specialists, which provides the functional stability of forest ecosystems (Sitzia et al 2017).…”
Section: Taxonomical Measures Reflect Between-year Differences and Variation In Assemblage Compositionsupporting
confidence: 52%
“…In our study, formerly managed forest reserves (established around 50 years ago) and forests under standard forest management appeared to be similar in terms of total and mean species richness of all fungal OTUs, as well as OTUs assigned to different functional trophic groups (Figures 1 and 2). Thus, our results support our first hypothesis and corroborate the limited number of studies based on surveys of sporocarps or soil DNA analyses that revealed high similarity in fungal richness in formerly managed forest reserves compared to nonintensively managed forests [29,[68][69][70]. However, the Jackknife extrapolated fungal OTU richness yielded slightly more fungal OTUs in forest reserves (643) than in corresponding managed forests (617).…”
Section: Overall Taxa Richness and Diversity Of Trophic Groupssupporting
confidence: 88%
“…Direct comparisons of different taxa sampled in the same sets of plots are often used to obtain deeper insight into the effects of various factors and processes on communities (e.g. Lososová et al, 2011;Chytrý et al, 2012;Sitzia et al, 2017;Burrascano et al, 2018). In this study, we found a common responseto fencing at the community level for vascular plants and oribatids in Mediterranean coastal pine forests.…”
Section: Responses Ofcommunity Composition and Soil Properties To Fen...supporting
confidence: 56%